Analisis Manajemen Produksi Dalam Mempertahankan Loyalitas Pelanggan Menurut Perspektif Ekonomi Islam: Studi Pada Usaha Kuliner Lindekss Sopto Di Kelurahan Talang Bakung Kecamatan Pall Merah Kota Jambi - Satlina Novrita Ep; Faturahman Faturahman; Beid Fitrianova Andriani (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2023)
This study aims to determine production management in maintaining customer loyalty and what obstacles are faced in the sopto talang bakung index food stall business. The type of research method used is qualitative research with the object of research at the sopto index food stall. In the process of collecting data in this study using observation, interview and documentation techniques. The results of this study show that production management applied by owners of sopto index food stalls such as production planning, organizing, mobilizing and controlling production in maintaining customer loyalty is done well and in accordance with the Islamic economic perspective and the constraints faced by sopto index food stalls are inflation of raw material prices, places and production equipment used are still traditional and when they want to develop new products.